2022
DOI: 10.3390/ijms23062964
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Intestinal Alkaline Phosphatase Treatment with Moderate Physical Activity Alleviates the Severity of Experimental Colitis in Obese Mice via Modulation of Gut Microbiota, Attenuation of Proinflammatory Cytokines, Oxidative Stress Biomarkers and DNA Oxidative Damage in Colonic Mucosa

Abstract: Inflammatory bowel diseases (IBD) are commonly considered as Crohn’s disease and ulcerative colitis, but the possibility that the alterations in gut microbiota and oxidative stress may affect the course of experimental colitis in obese physically exercising mice treated with the intestinal alkaline phosphatase (IAP) has been little elucidated. Mice fed a high-fat-diet (HFD) or normal diet (ND) for 14 weeks were randomly assigned to exercise on spinning wheels (SW) for 7 weeks and treated with IAP followed by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 91 publications
(114 reference statements)
6
30
0
Order By: Relevance
“…In addition, species of this genus display cellulolytic activity and may degrade LPS. Furthermore, different Ruminococcus species produce alkaline phosphatase [34], which improves gut barrier functions and detoxifies LPS, thereby preventing activation of NINONS pathways [49,50]. One could, therefore, hypothesize that depletion of this genus may have contributed to lowered LPS breakdown and thus increased translocation of LPS in MDD particularly when deficits in tight junctions are present [13][14][15][16].…”
Section: Is Depletion Of Ruminococcus Important To Mdd?mentioning
confidence: 99%
“…In addition, species of this genus display cellulolytic activity and may degrade LPS. Furthermore, different Ruminococcus species produce alkaline phosphatase [34], which improves gut barrier functions and detoxifies LPS, thereby preventing activation of NINONS pathways [49,50]. One could, therefore, hypothesize that depletion of this genus may have contributed to lowered LPS breakdown and thus increased translocation of LPS in MDD particularly when deficits in tight junctions are present [13][14][15][16].…”
Section: Is Depletion Of Ruminococcus Important To Mdd?mentioning
confidence: 99%
“…Oxidant stress exerts a crucial action in pathophysiology of UC ( Wojcik-Grzybek et al, 2022 ). Studies have revealed that increased production of ROS destroys the cellular macromolecules (DNA, lipids and proteins) and breaks epithelia cell integrality ( Juan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…165 IAP can alleviate myocardial ischemia and reperfusion injury by inhibiting inflammatory response and reducing oxidative stress. 166 IAP can reduce the risk of cardiac events by regulating intestinal barrier function and reducing the entry of gut-derived endotoxins. 9 Additionally, IAP can also affect lipid levels by regulating cholesterol metabolism and lipid absorption, thus influencing cardiovascular development.…”
Section: Ischemic Heart Disease (Ihd)mentioning
confidence: 99%
“…Recent studies found a clear correlation between IAP deficiency and IHD . IAP can alleviate myocardial ischemia and reperfusion injury by inhibiting inflammatory response and reducing oxidative stress . IAP can reduce the risk of cardiac events by regulating intestinal barrier function and reducing the entry of gut-derived endotoxins .…”
Section: Iap As An Indicator Of Intestinal Barrier Related Disease As...mentioning
confidence: 99%